Uso de nutrición parenteral total en pacientes con fístula enterocutánea hospitalizados en el Hospital Essalud Víctor Lazarte Echegaray - Trujillo, enero – diciembre 2017 - Cruz Flores, Kevin Elvis (2018)
The main objective of this report on pre-professional practices was to evaluate the use of total parenteral nutrition (TPN) in patients with enterocutaneous fístula (ECF) registered in the Nutritional Metabolic Support Unit (USMEN) of the Essalud Hospital Víctor Lazarte Echegaray - Trujillo, January - December 2017. The medical prescriptions of 10 patients were analyzed where it was observed that the volumes of the nutritional requirements presented changes according to the evolution in each patient with enterocutaneous fístulas and that 70% of the patients who received TPN presented a favorable evolution and 30% of patients with oncological problems presented a stationary evolution and up to 45 days of treatment with TPN, while 8 days of treatment in patients with uncomplicated pathologies